2014
DOI: 10.1073/pnas.1316848111
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction of fluid stresses governs 3D cell migration

Abstract: Solid tumors are characterized by high interstitial fluid pressure, which drives fluid efflux from the tumor core. Tumor-associated interstitial flow (IF) at a rate of ∼3 μm/s has been shown to induce cell migration in the upstream direction (rheotaxis). However, the molecular biophysical mechanism that underlies upstream cell polarization and rheotaxis remains unclear. We developed a microfluidic platform to investigate the effects of IF fluid stresses imparted on cells embedded within a collagen type I hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(236 citation statements)
references
References 45 publications
8
215
3
Order By: Relevance
“…In the future, investigating the role of IFF on 3D DCIS structures in a more clinically relevant matrix will lead to better understanding of the role of IFF on breast cancer invasion. We must also consider the contribution of other proposed mechanisms of IFF mechanotransduction, including mechanosensors such as integrins and the tumor cell glycocalyx, which have both been implicated in IFF-induced cell invasion (17,19). Examining these other mechanisms may help identify the upstream mediator of PI3K phosphorylation in NeuN cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, investigating the role of IFF on 3D DCIS structures in a more clinically relevant matrix will lead to better understanding of the role of IFF on breast cancer invasion. We must also consider the contribution of other proposed mechanisms of IFF mechanotransduction, including mechanosensors such as integrins and the tumor cell glycocalyx, which have both been implicated in IFF-induced cell invasion (17,19). Examining these other mechanisms may help identify the upstream mediator of PI3K phosphorylation in NeuN cells.…”
Section: Discussionmentioning
confidence: 99%
“…In metastatic cells, IFF altered extracellular chemokine gradients to accelerate tumor cell invasion via CXCR4-and CCR7-dependent chemotaxis (14,15), and increased MMP activity via shear stress sensing through the glycocalyx (17). More recently, IFF was shown to induce invasion against the direction of flow due to fluid drag forces and activation of integrins on the upstream side of the cell (19). Although we know some of its effects on invasive cells, the specific pathways triggered by IFF are still unclear, especially those that play a crucial role in the early stages of invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical forces also contribute to control of capillary cell growth, migration and fate determination Mammoto et al, 2012), and changes in mechanical forces elicited by altering ECM stiffness can regulate angiogenesis through p190RhoGAP . Given that paxillin mediates force-dependent control of cell behaviors (Sawada and Sheetz, 2002;Zaidel-Bar et al, 2007), including directional cell motility (Plotnikov et al, 2012;Polacheck et al, 2014;Sero et al, 2011), cell-derived mechanical forces might also contribute to the control of angiogenesis through paxillin.…”
Section: Discussionmentioning
confidence: 99%
“…In human tumors, the collagen component can be even greater (13). The increase in collagen content within the extracellular matrix contributes to tumor cell movement (14) and metastasis.…”
Section: Consequences Of Hyperpermeabilitymentioning
confidence: 99%
“…Studies in human tumor xenografts have verified that effects of IFP on radiation response are independent of extent of hypoxia (28). Recent studies have revealed that IFP increases tumor cell aggression by activating signal transduction pathways that promote epithelial-mesenchymal transition (29) and cell motility (14).…”
Section: Hyperpermeability Contributes To Elevated Interstitial Fluidmentioning
confidence: 99%